Taking a wider view on climate governance: moving beyond the 'iceberg, ' the 'elephant, ' and the 'forest'. (23rd March 2016) - Aykut, Stefan C.
Abstract : Attention in the literature on global climate politics has recently turned from a focus on intergovernmental negotiations to conceptualizing climate governance 'beyond' or 'outside' the UN regime. However, this literature differs on three key aspects: the underlying research paradigms, what is identified as the heart of the problem, and proposed solutions. One group of scholars calls for an attention shift from the 'tip of the iceberg' of climate governance to its much larger 'hidden parts, ' conceptualized through notions such as the 'climate change regime complex, ' a 'fragmented climate governance architecture, ' and 'transnational climate governance.' A second set of authors points to the 'elephant in the room, ' namely underlying power structures and material configurations in the international system that block effective responses to the climate crisis. A third group has argued that instead of looking at the individual 'trees' of climate negotiations, research should focus on the 'forest' of climate governance, made up of framings, norms, and emerging 'climate governmentalities.' The article proposes the concept of a 'schism of reality' as a means to overcome this fragmentation of the literature. This notion offers a new way of understanding interactions between the climate regime and its wider environment by focusing on discrepancies and contradictions. It accommodates different theoretical perspectives and provides common ground for future research: on how paradoxes and contradictions are dealt with in climate governance; how they can be overcome; how current developments in climate governance reduce the schism; and where and why aspects of the schism persist. WIREs Clim Change 2016, 7:318–328. doi: 10.1002/wcc.391 This article is categorized under: Policy and Governance > International Policy Framework